Passions Pedagogies and 21st Century Technologies - Hawisher, Gail (University Press of Colorado, 1999)
Gail Hawisher and Cynthia Selfe created a volume that set the agenda in the field of computers and composition scholarship for a decade. The technology changes that scholars of composition studies faced as the new century opened couldn't have been more deserving of passionate study. While we have always used technologies (e.g., the pencil) to communicate with each other, the electronic technologies we now use have changed the world in ways that we have yet to identify or appreciate fully. Likewise, the study of language and literate exchange, even our understanding of terms like literacy, text, and visual, has changed beyond recognition, challenging even our capacity to articulate them. As Hawisher, Selfe, and their contributors engage these challenges and explore their importance, they "find themselves engaged in the messy, contradictory, and fascinating work of understanding how to live in a new world and a new century." The result is a broad, deep, and rewarding anthology of work still among the standard works of computers and composition study.